Plasma cytokines, chemokines and cellular immune responses in preschool Nigerian children infected with Plasmodium falciparum - HOLLAND, CELIA (My University, 2013)
BACKGROUND: Malaria is a major cause of morbidity and mortality worldwide with over one million deaths annually, particularly in children under five years. This study was the first to examine plasma cytokines, chemokines and cellular immune responses in pre-school Nigerian children infected with Plasmodium falciparum from four semi-urban villages near Ile-Ife, Osun State, Nigeria. METHODS: Blood was obtained from 231 children (aged 39-73 months) who were classified according to mean P. falciparum density per μl of blood (uninfected (n = 89), low density (<1,000, n = 51), medium density (1,000-10,000, n = 65) and high density (>10,000, n = 22)). IL-12p70, IL-10, Nitric oxide, IFN-γ, TNF, IL-17, IL-4 and TGF-β, C-C chemokine RANTES, MMP-8 and TIMP-1 were measured in plasma. Peripheral blood mononuclear cells were obtained and examined markers of innate immune cells (CD14, CD36, CD56, CD54, CD11c AND HLA-DR). T-cell sub-populations (CD4, CD3 and γδTCR) were intracellularly stained for IL-10, IFN-γ and TNF following polyclonal stimulation or stimulated with malaria parasites. Ascaris lumbricoides was endemic in these villages and all data were analysed taking into account the potential impact of bystander helminth infection. All data were analysed using SPSS 15 for windows and in all tests, p <0.05 was deemed significant. RESULTS: The level of P. falciparum parasitaemia was positively associated with plasma IL-10 and negatively associated with IL-12p70. The percentage of monocytes was significantly decreased in malaria-infected individuals while malaria parasitaemia was positively associated with increasing percentages of CD54+, CD11c+ and CD56+ cell populations. No association was observed in cytokine expression in mitogen-activated T-cell populations between groups and no malaria specific immune responses were detected. Although A. lumbricoides is endemic in these villages, an analysis of the data showed no impact of this helminth infection on P. falciparum parasitaemia or on immune responses associated with P. falciparum infection. CONCLUSIONS: These findings indicate that Nigerian children infected with P. falciparum exhibit immune responses associated with active malaria infection and these responses were positively associated with increased P. falciparum parasitaemia.
PUBLISHED
Keywords: Cytokines; Immunology, Inflammation & Infection